2020
DOI: 10.22161/ijels.54.20
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of English Schwa Realization by Muna Language Speaker

Abstract: English schwa, a short vowel with mid-central quality, is absent in phonological system of Muna language. When a sound does not exist in one language, the speaker of the language tends to replace the sound with another similar sound, or eliminate the sound, or add a sound to make it possible to realize. Hence, in Muna language, there are only five vowels without varying long and short vowels, while there are 20 phonetic vowel symbols in Received Pronunciation and 16 in General American. Thus, this study attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although Indonesians pronounce schwa as a long "a" the tests used in this study do not guarantee that they understand what they read. Indrayani & Nugraha (2020) claimed that some English schwa words sound like a mid-central vowel in Muna that the speaker recognises as a close variant of Schwa [ə]. asserted that the findings contradict the notion that schwa's position is only influenced by the context in which it appears.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Indonesians pronounce schwa as a long "a" the tests used in this study do not guarantee that they understand what they read. Indrayani & Nugraha (2020) claimed that some English schwa words sound like a mid-central vowel in Muna that the speaker recognises as a close variant of Schwa [ə]. asserted that the findings contradict the notion that schwa's position is only influenced by the context in which it appears.…”
Section: Resultsmentioning
confidence: 99%
“…Despite Indonesians pronouncing the word schwa as a long "a," the tests utilised in this study do not ensure that participants comprehend what they read. Indrayani and Nugraha (2020) reported that the English schwa, a short vowel with a mid-central character, is absent from the Muna language. This study aims to investigate the situations under which speakers of the Muna language can grasp the non-existent English schwa.…”
Section: Schwa Sound In English | ʃWɑ: |mentioning
confidence: 99%